EVALUATION OF LEUCAS ASPERA WHOLE PLANT EXTRACTS FOR DIURETIC AND LAXATIVE PROPERTY - TAMBE VIJAY D; Vishal B, Tambe; Ravindra S, Jadhav (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: This study was undertaken to investigate diuretic and laxative potency of Leucas aspera whole plant. Methods: The dried whole plant (leaves, stems, and flowers) material was subjected to extraction by continuous hot percolation method. In evaluation of diuretic activity male albino rats were used as the experimental animals. The first group of animals, serving as control, received normal saline (25 ml/kg, post-operative); the second group received furosemide (10 mg/kg, post-operative) in saline. Other groups received doses of extract (200-400 mg/kg) in normal saline. The parameters determined were total urine volume, the concentration of Na (chloride) in the urine. Na + and K + concentrations were determined by flame photometer, and Cl âˆ’ + (sodium), K concentration was estimated by titrimetric method. Laxative activity was also studied using male albino rats. The animal groups were administered orally either with vehicle (1% Tween-80 solution in normal saline, 25 ml/kg), reference standard drug, agar-agar (300 mg/kg, post-operative) in saline or doses of extract (200-400 mg/kg). After 8 h of drug treatment, the feces were collected and weighed. Results: This study revealed that L. aspera whole plant extracts possesses significant diuretic and laxative activity in comparison with the standard drugs. The activity may be due to the chemical constituent present in the plant parts. The further studies may be taken up to isolate these active constituents. Conclusion: L. aspera whole plant possesses diuretic and laxative property since it contains a variety of phytoconstituents. Keywords: Leucas aspera, Diuretics activity, Lipchitz method, Laxative activity, Furosemide, Agar-agar. + (potassium), and Cl âˆ’